2019
DOI: 10.2147/cmar.s207959
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identifying risk factors for high-dose methotrexate-induced toxicities in children with acute lymphoblastic leukemia</p>

Abstract: Background Whether monitoring of the methotrexate (MTX) concentrations after high-dose MTX (HD-MTX) infusion can predict toxicities is still controversial, especially when HD-MTX therapy is used in the treatment of children with acute lymphoblastic leukemia (ALL), which is different than the previous schedules. The relationship between patient characteristics and severe adverse events (AEs) has yet to be determined. Objective To analyze the relationship between the MTX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
(39 reference statements)
0
22
0
Order By: Relevance
“…High-dose methotrexate has been a key component of standard-of-care treatment for osteosarcoma since the 1970s, based on small cohort clinical trials that measured levels of tumor necrosis at the time of surgery ( Grem et al, 1988 ; Rosen et al, 1974 , 1979 ). Although these trials showed that most patients demonstrated little viable tumor tissue with methotrexate treatment, it was noted that high levels of toxicity were associated with this treatment ( Li et al, 2019 ; Perez et al, 1978 ; Rosen et al, 1974 , 1979 ). The doses required for histologic response were as high as 8–20 g/m 2 , which can result in kidney injury or liver toxicity, especially in adult patients ( Howard et al, 2016 ; Rosen et al, 1974 ; Wippel et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…High-dose methotrexate has been a key component of standard-of-care treatment for osteosarcoma since the 1970s, based on small cohort clinical trials that measured levels of tumor necrosis at the time of surgery ( Grem et al, 1988 ; Rosen et al, 1974 , 1979 ). Although these trials showed that most patients demonstrated little viable tumor tissue with methotrexate treatment, it was noted that high levels of toxicity were associated with this treatment ( Li et al, 2019 ; Perez et al, 1978 ; Rosen et al, 1974 , 1979 ). The doses required for histologic response were as high as 8–20 g/m 2 , which can result in kidney injury or liver toxicity, especially in adult patients ( Howard et al, 2016 ; Rosen et al, 1974 ; Wippel et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These factors may be due to higher MTX levels after multiple HDMTX cycles or other factors. The previous studies offered contradictory findings about several factors participate in this association such as; (Hoekstra, Van Ede et al 2003, Li, Sui et al 2019, Mandal, Samaddar et al 2020, Young, Cheng et al 2020. MTX level wouldn't predict appearance specific type of toxicity except nephrotoxicity after multiple HDMTX cycles, described by (Tsurusawa, Gosho et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…The solubilities of these metabolites in urine may reach ten folds lower than MTX (Schmiegelow 2009).The sequel may cause renal tubules obstruction, and extended contact of MTX with the renal tubular epithelial tissue lining exposes it to direct toxic harm and acute kidney injury(AKI) (Perazella and Moeckel 2010). LR cannot prevent nephrotoxicity (Li, Sui et al 2019), so Patients in group 2 who are at greater risk of irreversible acute kidney failure are expected to increase their serum creatinine by more than 50% within 24-hour ). The strong point in our study has a large sample size that proved the toxicity associated with SNPs, as consistent with recommendations of.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are retrospective and heterogeneous with varying use of supportive measures. 4,7,8 Therefore, we decided to study factors affecting HMN prospectively in a center where serial MTX monitoring as per protocol is not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of studies in children and adults on the various factors affecting HMN, especially when serial MTX levels are not being monitored. These studies are retrospective and heterogeneous with varying use of supportive measures 4,7,8 . Therefore, we decided to study factors affecting HMN prospectively in a center where serial MTX monitoring as per protocol is not feasible.…”
Section: Introductionmentioning
confidence: 99%